Surrogate insulin resistance indices are associated with left atrial thrombus in patients with nonvalvular atrial fibrillation - Zhou, You; Song, Xuewen; Ma, Jifang; Wang, Xianqing; Fu, Haixia (Frontiers in Aging, 2025)
IntroductionAtrial fibrillation is the most common cardiac arrhythmia with increased risk of thromboembolic events. Surrogate insulin resistance indices, triglyceride glucose (TyG) index and triglyceride glucose-body mass index (TyG-BMI index), are predictors of adverse outcomes in patients with cardiovascular diseases. In this study, we aimed to determine the association between insulin resistance indices and left atrial thrombus (LAT) in patients with nonvalvular atrial fibrillation (NVAF).MethodsA total of 466 patients with documented NVAF who underwent transesophageal echocardiography were studied retrospectively. Demographic data, laboratory results, echocardiographic measurements and medication were collected. Logistic regression analysis was performed to determine the association between insulin resistance indices and risk of LAT. C-statistic was calculated to determine the incremental value of insulin resistance indices in predicting LAT compared with CHA2DS2-VASc score.ResultsLAT were identified in 46 patients (9.87%). In the full adjustment model, elevated TyG index [per 1 standard deviation (SD) increment; odds ratio (OR): 1.588; 95% confidence interval (CI): 1.125-2.241, P = 0.009] and TyG-BMI index (per 1 SD increment; OR: 1.570; 95% CI: 1.142-2.160, P = 0.005) were significantly associated with high risk of LAT. Compared to the lowest quartile, ORs for the highest quartile were 3.691 (95% CI: 1.126-12.096, P = 0.031) for TyG index and 10.302 (95% CI: 2.232-47.556, P = 0.003) for TyG-BMI index. Compared with the CHA2DS2-VASc score alone, insulin resistance indices incorporated into the CHA2DS2-VASc score remain the predictive ability of LAT.ConclusionThe present study suggests that TyG index and TyG-BMI index are new predictors for LAT in patients with NVAF.